2021
DOI: 10.1590/1980-57642021dn15-030011
|View full text |Cite
|
Sign up to set email alerts
|

Depression and empathy in health professionals who work in the long-term care institutions for older adults

Abstract: Empathy is an important factor to guarantee the quality of care provided in the long-term care institutions (LTCIs) for older adults, and depression is a factor that affects the health of the professional and, consequently, the care. Thus, it is important that studies are conducted on the relationship of these variables in this context. Objective: The aim of this study is to verify the relationship between empathy and depressive symptoms among health professionals working in the LTCIs. Methods: A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…El deterioro o alteración de la salud mental puede perjudicar no solo su propia salud sino también la calidad de la asistencia prestada. (2) Si bien la empatía es uno de los principales factores que conducen a la calidad de la atención, el poco equilibrio, puede terminar causando daño a la salud de los profesionales.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…El deterioro o alteración de la salud mental puede perjudicar no solo su propia salud sino también la calidad de la asistencia prestada. (2) Si bien la empatía es uno de los principales factores que conducen a la calidad de la atención, el poco equilibrio, puede terminar causando daño a la salud de los profesionales.…”
Section: Introductionunclassified
“…Los profesionales de la salud que también presentan depresión tienen un mayor riesgo de experimentar agotamiento, lo que puede afectar negativamente la calidad de la atención prestada a los sujetos de atención. La prevalencia de depresión en este grupo fue del 19,8 %, lo que destaca la importancia de abordar adecuadamente la salud mental de los profesionales sanitarios (2). Resultados similares fueron descritos por Marshman et al(17) En cuanto a la empatía, se encontró que los profesionales con depresión mostraron niveles más altos de empatía, especialmente en el dominio emocional (18).…”
unclassified
“…For instance, a review showed that 25-75% of health-care professionals in geriatric settings are likely to experience burnout ( Sanchez et al, 2015 ). Also, a recent study conducted in Brazil showed that almost 20% of the professionals working in long-term care institutions for older adults experienced depression ( Borges et al, 2021 ). Other negative outcomes, such as poor quality of life and stress, have been found within this profession, in comparison to age- and sex-matched populations (see Costello et al, 2019 for a review).…”
Section: Introductionmentioning
confidence: 99%